Market power, industry concentration and trade liberalization: Evidence from Costa Rica - Felipe Gómez-Trejos; Daniela Córdoba Solano; Alberto Vindas Quesada (Inter-American Development Bank (IDB), 2025)
Research about trade liberalization's impact on markups has focused on manufacturing due to data availability considerations. How do these effects vary across sectors? Which industries become more and less competitive as trade barriers are eliminated? We leverage firm-level tax records from the universe of formal-sector businesses in Costa Rica with the 2009 trade liberalization as a natural experiment to evaluate its industry-specific effects on markups across all industries. We find negative effects on markups in agriculture, mining, electricity, water supply, and business services. Alternatively, the reform led to markup increases in accommodations and food services, information and communications, real estate, finance and insurance, and education, health, and social work. We do not observe statistically significant effects in manufacturing, transportation and storage, construction, and wholesale and retail trade. Our findings represent a more comprehensive evaluation of the potential pro-competitive effects from trade liberalization than existing studies exclusively focusing on manufacturing firms.
Keywords: D22; L11; F13; F14; 330; Market power; Markup; Costa Rica; Latin America; Trade; Liberalization; Tarif